SIMPLIFIED APPROACHES FOR MODELING INFILLED FRAMES (Advances in Civil and Architectural Engineering, 2021)
In many seismic areas, reinforced-concrete frames are filled with masonry infill walls. The behavior of these structural composite systems are difficult to model, and existing regulations lack guidelines for their design. In most cases, the masonry infill is excluded from the design process because it is considered a non-structural element. However, excluding them can have significant negative consequences. A properly modeled and designed reinforced-concrete frame with infill can significantly affect the strength, stiffness, and energy dissipation of the frame structure. In fact, a masonry infill combined with a relatively flexible reinforced-concrete frame certainly takes part in the resistance to horizontal actions. To investigate this issue, we modeled the behavior of frame structures with masonry infills in three ways: First, we used a linear seismic method of equivalent horizontal forces, applied to six models with different heights, modeling the masonry infill with “shell” finite elements. Second, we performed the same analysis with a “link” element as a compressive strut. Third, we used nonlinear dynamic analysis to consider the concentrated plasticity of columns and beams and a nonlinear model with the masonry infill considered a compressive strut. In each modeling approach, the masonry infill significantly affected the behavior of the structures and their dynamic response to seismic actions.